Muttering Contempt and Smiling Appreciation: Disentangling the History of the Reaction Object Construction in English. Issue 2 (17th February 2017) - Bouso, Tamara
ABSTRACT: Structures such as "she muttered contempt" or "she smiled appreciation" have been referred to as Reaction Object Constructions (ROCs), and consist of a normally intransitive verb followed by an object that conveys an emotion, such that the whole construction can be paraphrased as "express an emotion by V-ing". Although ROCs have been discussed recently in relation to Present Day English, from a historical perspective they have received very little attention, mentioned only in passing in historical reference grammars. This paper explores aspects of the history of ROCs, drawing on data from the Oxford English Dictionary and the Corpus of Late Modern English Texts, version 3.0 . The findings show that, similarly to other processes of transitivisation such as the way-construction, ROCs have been in use since the fifteenth century, expanding to more verbs over the course of the Late Modern English period. More specifically, the data suggests that the construction was established mainly in the nineteenth century, a period in which those verbs attested in the construction became quite fashionable in novels. Findings are also subjected to a collexeme analysis, revealing the prototypical verbs of the construction during this period.